Analysis of knowledge management implementation models for a business incubator - Damian, Ieda Pelógia Martins [UNESP]; Zancheta, Flávia Helena Barioni; Igarashi, Reinaldo Tsuyoshi; Marques, Dalton Siqueira Pitta (My University, 2019)
Knowledge has been occupying a prominent position both in the organizational context and in the academic context, especially in the area of Information Science. In order for organizations to benefit from the benefits of knowledge, it must be properly managed. For this, there are models in the literature for the implantation of knowledge management; however, the majority of these models is directed to big private companies. In view of this scenario, this research aims to analyze the most appropriate model for the implementation of knowledge management for an incubator business of public sector. For that, a bibliographic survey was carried out on the main models of knowledge management implementation so that its characteristics, its components and its methodologies could be evaluated. According to the results, it was possible to verify that the characteristics that differentiate public organizations from private organizations influence the choice of the most appropriate model for the implementation of knowledge management. Thus, this research concludes that the most appropriate model for the implementation of knowledge management for business incubators surveyed that belongs to the public sector is the Knowledge Management Model for the Brazilian Public Administration.
Análisis de modelos de implementación de gestión de conocimiento para una incubadora de empresas
Análise de modelos de implantação da gestão do conhecimento para uma incubadora de empresas
Keywords: Business incubator; Implantation models; Knowledge management; Public administration